Bioremediation based on palm oil sludge as an intervention for heavy metal pollution risk in industrial residential - Azrial, Fahmi; Sahdan, Fahrizal; Putri, Okta Angelia; Listiana, Ika (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The palm oil industry in Indonesia, often pollution the environment, especially water bodies, with waste containing hazardous metals. This can threaten the lives of aquatic organisms and damage ecosystems. Although the palm oil industry has become a pillar of the national economy with production reaching 46,986 tons in 2023, the waste problems generated, especially palm oil sludge, demand innovative and sustainable solutions. The limitations of existing technologies in handling heavy metal pollution drive the need for an interdisciplinary approach that not only reduces environmental risks but also provides economic added value through circular economy concepts and local resource empowerment. The aim of this study is to identify the characteristics of palm oil sludge-based bioremediation stones in the process of heavy metal adsorption. Methods: This study was conducted through descriptive analytical literature review with a qualitative approach. Findings: The results show that palm oil sludge-based bioremediation stones have microporosity characteristics and complex chemical compositions capable of absorbing heavy metals with efficiency reaching 85-92%. This innovation not only offers sustainable solutions, but also provides multidimensional benefits, including reduced public health risks and the creation of circular economic models. Conclusion: Through activation with sulfuric acid, the potential for heavy metal absorption can be increased by up to 35%, which implies a 70% reduction in environmental contamination in industrial areas. Novelty/Originality of this article: This innovation integrates an interdisciplinary approach combining environmental science, chemistry, and resource management, potentially creating a replicable risk intervention model for industrial areas, with economic value.